Boys in school and society - Cresswell, John, 1950- (ACER, 2002)
In the past decade there has been a growing perception in Australiathat girls have become more successful pursuing their educationalgoals than boys - especially in educational outcomes relating toliteracy. In addition there is evidence from a range of studies that boysregard their school experience less favourably than girls and are lessstrongly engaged in the work of schools. This paper focuses onstudents' achievement and attitudes to school, and the influences thatshape different outcomes for boys and girls. Beyond school, a smallerproportion of boys than girls progress to higher education.
Keywords: Boys -- Education -- Australia.; Sex role in children -- Australia.; Garçons -- Éducation -- Australie.; Rôle selon le sexe chez l'enfant -- Australie.; EDUCATION -- Secondary.; EDUCATION -- Students & Student Life.; Boys -- Education; Sex role in children; Australia